Dakwah Kebangsaan TQN PPS Sirnarasa dalam Penguatan Kohesi Sosial di Indonesia - Feriyanto Feriyanto; Ucup Fathudin Al-Maarif; Opik Jamaludin; Dadang Muliawan (Anida (Aktualisasi Nuansa Ilmu Dakwah), 2026)
This study aims to reconstruct a Community-Based Da’wa (CBD) model rooted in the phenomenological experience of practitioners of the Qadiriyya-Naqshbandiyya Sufi Order (TQN) at Pondok Pesantren Sirnarasa, Ciamis. The research employs Moustakas’s transcendental phenomenology with epoche reduction, horizonalization, thematic clustering, and textural-structural description. Data were collected through in-depth interviews with eleven purposively selected informants, six-month participatory observation across seven monthly gatherings, and documentary study, while validity was secured through source-method triangulation, member checking, and audit trail. The findings reveal four invariant structures: (1) dhikr jahr–khafi as a personal–collective transformative da’wa mechanism; (2) Madrasah Roudloh as cross-identity bridging-capital infrastructure; (3) semantic integration of Pancasila and Sufism constructing religious nationalism; and (4) a trajectory transforming the order from al-thariqah ila Allah toward al-thariqah ila al-ummah. The synthesis yields a three-component CBD model—spiritual foundation, ritual mediation, social engagement—that extends cultural da’wa theory by integrating Durkheim’s solidarity theory, Putnam’s social capital framework, and Collins’s interaction ritual chains. The study contributes a paradigmatic alternative for developing nationalist da’wa amid Indonesia’s contemporary multicultural polarization and has practical implications for revitalizing tarekat as strategic actors in strengthening social cohesion.